PROFESSIONAL KNOWLEDGE “FROM THE FIELD”: ENACTING PROFESSIONAL LEARNING IN THE CONTEXTS OF PRACTICE - Riveros, Augusto; Viczko, Melody (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2012)
Based on a qualitative case study that examined elementary teachers’ understandings of a professional development policy, we question the conceptual disconnection between professional learning and professional practices in some conceptualizations of professional learning communities. We analyse the research data using Actor-Network Theory and report that the teachers in the case study perceived a disconnection between the scenarios of professional knowledge creation and the scenarios of professional practice. Such disconnection is exacerbated due to an ambiguous treatment of the concept of professional practice in the policy documents that endorse the idea of professional learning communities. We conclude that a key element in the transformation of professional practices is the teacher’s awareness that his/her professional knowledge is enacted through his/her actions and practices; thereby concluding that professional learning is situated in the context of professional practices. SAVOIR PROFESSIONNEL “DE TERRAIN”: IMPOSER LA FORMATION PROFESSIONNELLE DANS UN CONTEXTE PRATIQUE Faisant suite à une étude de cas qualitative étudiant la compréhension d’enseignants du primaire à l’égard d’une politique de développement professionnel, nous questionnons la coupure conceptuelle existant entre la formation en milieu de travail et les pratiques professionnelles au cœur de certaines conceptualisations d’une communauté de formation professionnelle. Nous analysons les données de recherche en utilisant la Théorie de l’Acteur-Réseau. Nous révélons que les enseignants participant à l’étude de cas ont perçu une différence entre les scénarios de création de savoir professionnel et ceux de pratique professionnelle. Une telle coupure est exacerbée par l’utilisation ambiguë du concept de pratique professionnelle qui, dans les documents formulant les politiques, soutient l’idée de communautés professionnelles d’apprentissage. Nous en concluons qu’un élément-clé de la transformation des pratiques professionnelles réside dans la prise de conscience, par les enseignants, que leur savoir professionnel est activé à travers leurs actions et pratiques et est donc, au cœur de leurs pratique professionnelle.